An analytical model for the self-bias magnetoelectric effect of magnetization-graded magnetoelectric composites. (15th November 2022) - Shi, Yang; Lei, Baoxin; Wang, Yongkun; Ye, Junjie
Abstract: This paper presents an analytical model to evaluate the self-bias magnetoelectric (ME) effect of magnetization-graded ME composites under extensional-bending coupled vibration. The distribution of the self-bias magnetic field produced inside ME composites is quantitatively analyzed based on the molecular current model. Sequentially, a multi-field coupled ME model is developed using equivalent nonlinear constitutive relations, extensional-bending coupled equations, and Maxwell's equations simultaneously. The developed ME theory is highlighted with a direct comparison with experiments that shows their close agreement. The results indicate that an available self-bias magnetic field is produced in the magnetization-graded composites, which in turn induces a self-bias ME coupling at zero bias magnetic field. It is also demonstrated that, with applying tensile stress or appropriately increasing the thickness of the high-permeability layer, the self-bias ME coefficient can be enhanced and account for more than 55% of the maximum one, and the resonance frequency is regulated in a wide range. In addition, the competitive relationship between the influence of mechanical and magnetic properties of high-permeability materials on self-bias ME coupling is revealed. Given the significance of this study, it may be utilized in the development of high-performance self-bias ME devices.